The Metabolomic View of Systemic Sclerosis—A Systematic Literature Review - Sebastian T. Jendrek; Franziska Schmelter; Christian Sina; Ulrich L. Günther; Gabriela Riemekasten (Sclerosis, 2025)
The mortality risk in systemic sclerosis (SSc) is primarily determined by pulmonary involvement (interstitial lung disease (ILD), pulmonary fibrosis), pulmonary arterial hypertension (PAH), and cardiac involvement. With timely and intensive treatment, the disease can be halted or even improved. Therefore, early diagnosis remains crucial. Unfortunately, biomarkers currently available cannot meet this requirement. SSc is characterized by autoimmune inflammation, vasculopathy, and fibrosis. The immunometabolic characterization of autoimmune diseases contributes to a better understanding of the underlying inflammatory processes. In this narrative review, we included 13 studies on metabolomic patterns in SSc in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Guidelines (PRISMA). Current studies indicate an altered metabolome in SSc. All documented significant differences between patients with SSc and healthy controls, although the observed metabolomic patterns in SSc were inconsistent between studies. Metabolome alterations include, in particular, energy-related metabolic pathways such as glycolysis/gluconeogenesis, including the synthesis and degradation of ketones, fatty acid oxidation, amino acid-related metabolic pathways, lipid metabolism, and the tricarboxylic acid (TCA) cycle, including pyruvate metabolism. The most frequently examined organ complications with reported significant aberrations of the metabolome were skin involvement, ILD, and PAH. Conclusion: The detailed characterization of the SSc-specific metabolome promises a more comprehensive understanding of the pathogenic mechanisms of the disease. Furthermore, the detection of associations between specific metabolic aberrations and disease phenotypes bears hope for new biomarkers and an improved personalized approach to diagnostics, therapy, and follow-up in the management of SSc.